Battery and liquid injection method thereof, energy storage device and power utilization system

By designing the localized distribution of lithium salts in the electrolyte in lithium-ion batteries, the energy loss problem caused by electrochemical polarization and concentration polarization is solved, and the battery cycle energy efficiency and capacity retention rate are improved.

CN119833761APending Publication Date: 2025-04-15XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803166.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The energy loss caused by electrochemical polarization and concentration polarization during the circulation process limits the economic benefits of energy storage power plants.

Method used

By designing the localized distribution of different types of lithium salts and mass proportions in free electrolytes and non-free electrolytes, the energy loss caused by electrochemical polarization and concentration polarization is reduced. The specific method is to control the inorganic lithium salt in the free electrolyte and ensure the participation of the organic lithium salt in the non-free electrolyte, and optimize the battery performance by limiting the specific lithium salt content ratio.

Benefits of technology

It effectively improves the battery's cycle energy efficiency and cycle capacity retention rate, significantly reduces energy losses, and improves the economic benefits of energy storage power plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the field of energy storage, and particularly discloses a battery and a liquid injection method thereof, an energy storage device and a power utilization system.The battery comprises a positive pole piece, a negative pole piece, a diaphragm and electrolyte, the electrolyte comprises free electrolyte and non-free electrolyte, the free electrolyte comprises first lithium salt and second lithium salt, the first lithium salt is inorganic lithium salt, and the second lithium salt is inorganic lithium salt; the second lithium salt is an organic lithium salt, the mass ratio of the first lithium salt in the free electrolyte is m1%, and the mass ratio of the second lithium salt in the free electrolyte is m2%; the non-free electrolyte comprises a first lithium salt and a second lithium salt, the mass ratio of the first lithium salt in the non-free electrolyte is n1%, the mass ratio of the second lithium salt in the non-free electrolyte is n2%, and m < 2 > / m1-n2 / n1 is larger than-0.8 and smaller than 0.2, m < 2 > / m1 is larger than or equal to 0.05 and smaller than 1, and n2 / n1 is larger than or equal to 0.1 and smaller than or equal to 5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of energy storage, and specifically relates to a battery and a liquid injection method thereof, an energy storage device and an electricity consumption system. Background Art

[0002] Lithium-ion batteries have the characteristics of low cost, high safety and long life, and have been widely used in the field of electrochemical energy storage power stations. The ratio of the discharge energy to the charging energy of lithium-ion batteries during the cycle is the round-trip energy efficiency (RTE). During the charging and discharging process, the internal resistance of the battery and the connector will consume part of the electrical energy. At the same time, the electrochemical polarization and concentration polarization during the lithium ion deintercalation process will also cause some energy loss. In the economic benefit calculation method of energy storage power stations, the cost is settled according to the grid output energy, and the income is settled according to the battery output energy. Therefore, RTE has become one of the important reasons restricting the cost recovery of energy storage power stations.

[0003] In the related art, the main ways to improve the battery RTE are: regulating the battery to work in a suitable SOC range through the battery control management system, and keeping the battery working close to room temperature through the temperature control system. However, the above methods have limited effect on improving the battery RTE and it is difficult to further improve the battery RTE. Summary of the invention

[0004] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one purpose of the present application is to propose a battery and its injection method, energy storage device and power system. The present application designs the localized distribution of different types and mass proportions of lithium salts in free electrolyte and non-free electrolyte, which is used to reduce the RTE loss caused by electrochemical polarization and concentration polarization, so as to achieve the purpose of improving the cycle energy efficiency (ie, RTE) and cycle capacity retention rate of the battery. Specifically, the present application designs inorganic lithium salts as the leading lithium salts in the free electrolyte, and ensures that there is a sufficient amount of organic lithium salts in the non-free electrolyte to participate in the solvation reaction, that is, by limiting -0.8<m2 / m1-n2 / n1<0.2, and 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5, to effectively achieve the purpose of improving the cycle energy efficiency (ie, RTE) and cycle capacity retention rate of the battery.

[0005] The first aspect of the present application provides a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator;

[0006] The free-state electrolyte includes a first lithium salt and a second lithium salt, the first lithium salt is an inorganic lithium salt, the second lithium salt is an organic lithium salt, the mass proportion of the first lithium salt in the free-state electrolyte is m1%, and the mass proportion of the second lithium salt in the free-state electrolyte is m2%; the non-free-state electrolyte includes a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the non-free-state electrolyte is n1%, and the mass proportion of the second lithium salt in the non-free-state electrolyte is n2%, satisfying -0.8<m2 / m1-n2 / n1<0.2, 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5.

[0007] According to the battery of the above embodiment of the present application, the present application designs the localized distribution of different types and mass proportions of lithium salts in the free electrolyte and the non-free electrolyte, which is used to reduce the RTE loss caused by electrochemical polarization and concentration polarization, so as to achieve the purpose of improving the cycle energy efficiency (ie, RTE) and cycle capacity retention rate of the battery. Specifically, the present application designs inorganic lithium salts as the leading lithium salts in the free electrolyte, and ensures that there is a sufficient amount of organic lithium salts in the non-free electrolyte to participate in the solvation reaction, that is, by limiting -0.8<m2 / m1-n2 / n1<0.2, and 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5, to effectively achieve the purpose of improving the cycle energy efficiency (ie, RTE) and cycle capacity retention rate of the battery.

[0008] In addition, the battery according to the above embodiment of the present application may also have the following additional technical features:

[0009] In some embodiments of the present application, the first lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate and lithium hexafluoroarsenate; and / or, the second lithium salt includes at least one of lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide and lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide.

[0010] In some embodiments of the present application, the electrolyte is formed by secondary injection, and the secondary injection includes one injection of electrolyte and two injections of electrolyte; the one injection of electrolyte includes a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the one injection of electrolyte is MA1%, and the mass proportion of the second lithium salt in the one injection of electrolyte is MB1%; the two injections of electrolyte include a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the two injections of electrolyte is MA2%, and the mass proportion of the second lithium salt in the two injections of electrolyte is MB2%, θ1=MB1% / MA1%, θ2=MB2% / MA2%, satisfying 0.05≤θ1≤1, 0≤θ2≤2, m2 / m1<θ1.

[0011] In some embodiments of the present application, 3≤MA1≤15, 5≤MA2≤15 are satisfied.

[0012] In some embodiments of the present application, 0.2≤θ1 / Min(σc,σa,σs)≤2, 0≤θ2 / Max(σc,σa,σs)≤5 are satisfied; wherein, Min(σc,σa,σs) represents the minimum value among σc, σa and σs, and Max(σc,σa,σs) represents the maximum value among σc, σa and σs; σc represents the porosity of the positive electrode sheet when the battery is in the SOC state of 0%; σa represents the porosity of the negative electrode sheet when the battery is in the SOC state of 0%; σs represents the porosity of the diaphragm when the battery is in the SOC state of 0%.

[0013] In some embodiments of the present application, 15%≤σc≤60%; and / or, 20%≤σa≤70%; and / or, 10%≤σs≤60% are satisfied.

[0014] The second aspect of the present application proposes a liquid injection method for a battery as described in the above embodiment. According to the embodiment of the present application, the liquid injection method includes:

[0015] Use one injection of electrolyte for the first injection, let it stand, and form;

[0016] Use two injections of electrolyte for the second injection, high temperature aging, and volume separation;

[0017] The first electrolyte includes a first lithium salt and a second lithium salt, and the second electrolyte includes a first lithium salt and a second lithium salt.

[0018] According to the injection method of the above-mentioned embodiment of the present application, the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage are separated by secondary injection, and the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery are flexibly controlled, which can effectively reduce the RTE loss caused by electrochemical polarization and concentration polarization, thereby effectively improving the battery's cycle energy efficiency (ie, RTE) and cycle capacity retention rate.

[0019] In addition, the liquid injection method according to the above embodiment of the present application may also have the following additional technical features:

[0020] In some embodiments of the present application, the mass proportion of the first lithium salt in the one injection of electrolyte is MA1%, the mass proportion of the second lithium salt in the one injection of electrolyte is MB1%, the mass proportion of the first lithium salt in the second injection of electrolyte is MA2%, the mass proportion of the second lithium salt in the second injection of electrolyte is MB2%, θ1=MB1% / MA1%, θ2=MB2% / MA2%, satisfying 0.05≤θ1≤1, 0≤θ2≤2, m2 / m1<θ1.

[0021] In some embodiments of the present application, a mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2).

[0022] In some embodiments of the present application, the injection coefficient of the sum of the first injection of electrolyte and the second injection of electrolyte is 3g / Ah to 5g / Ah.

[0023] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the injection method of the above embodiment. As a result, the energy storage device has excellent cycle energy efficiency (ie, RTE) and cycle capacity retention rate. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.

[0024] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric power equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric power equipment. As a result, the electric power system has excellent cycle energy efficiency (ie, RTE) and cycle capacity retention rate. It should be noted that the above-described features and advantages for the battery are also applicable to the electric power system and will not be repeated here.

[0025] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0026] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.

[0027] In a first aspect, the present application proposes a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the electrolyte includes a free electrolyte and a non-free electrolyte, the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator; the free electrolyte includes a first lithium salt and a second lithium salt, the first lithium salt is an inorganic lithium salt, the second lithium salt is an organic lithium salt, and the first lithium salt is an inorganic lithium salt. The mass proportion of the first lithium salt in the free electrolyte is m1%, and the mass proportion of the second lithium salt in the free electrolyte is m2%; the non-free electrolyte includes the first lithium salt and the second lithium salt, the mass proportion of the first lithium salt in the non-free electrolyte is n1%, and the mass proportion of the second lithium salt in the non-free electrolyte is n2%, satisfying -0.8<m2 / m1-n2 / n1<0.2, and 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5. Therefore, the present application designs the localized distribution of different types and mass proportions of lithium salts in the free electrolyte and the non-free electrolyte, which is used to reduce the RTE loss caused by electrochemical polarization and concentration polarization, so as to achieve the purpose of improving the cycle energy efficiency (ie, RTE) and cycle capacity retention rate of the battery. Specifically, the present application designs inorganic lithium salts as the dominant lithium salts in the free-state electrolyte, and ensures that there is a sufficient amount of organic lithium salts in the non-free-state electrolyte to participate in the solvation reaction, that is, by limiting -0.8<m2 / m1-n2 / n1<0.2, and 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5, to effectively achieve the purpose of improving the battery's cycle energy efficiency (ie, RTE) and cycle capacity retention rate.

[0028] The principle of the beneficial effect of the battery proposed in this application is described in detail below:

[0029] The electrolyte of the battery of the present application includes a free electrolyte and a non-free electrolyte. The non-free electrolyte includes the electrolyte in the pores of the positive electrode plate, the electrolyte in the pores of the negative electrode plate and the electrolyte in the pores of the diaphragm, and the rest is a free electrolyte. The free electrolyte and the non-free electrolyte both include a first lithium salt and a second lithium salt. The first lithium salt is an inorganic lithium salt, and the second lithium salt is an organic lithium salt. The inorganic lithium salt has the characteristics of a wide redox window and excellent dissociation ability, and the organic lithium salt has the characteristics of reducing to generate a SEI protective layer rich in inorganic and organic components.

[0030] The inventors found that during the formation and circulation process of the battery, a SEI negative electrode protective layer will be formed and a repair reaction will continue to occur. Different types of lithium salts have obvious differences in the stability and ion conductivity of the SEI negative electrode protective layer. At the same time, the lithium salt content also determines the solvation shell structure, affecting the dissociation and transmission of lithium ions. The inventors also found that there are local distribution differences in the types and contents of lithium salts in the electrolyte in the battery. Since the non-free electrolyte is stored in the pole piece and the pores of the diaphragm and is in direct contact with the pole piece and the diaphragm, the non-free electrolyte requires good film-forming ability and ion conductivity; the free electrolyte is distributed in the remaining space outside the material in the battery to supplement the amount of electrolyte required for long cycles, so it requires good ion transmission ability.

[0031] In view of this, the present application designs the localized distribution of different lithium salt types and mass proportions in free electrolyte and non-free electrolyte, which can effectively reduce the RTE loss caused by electrochemical polarization and concentration polarization, thereby achieving the purpose of improving the battery's cycle energy efficiency (ie, RTE) and cycle capacity retention rate.

[0032] According to the above characteristics, the present application designs inorganic lithium salts as the leading lithium salts in the free electrolyte, and a sufficient amount of organic lithium salts are required in the non-free electrolyte to participate in the solvation reaction. Taking into account the differences in the battery usage status, by limiting -0.8<m2 / m1-n2 / n1<0.2, and 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5, the purpose of improving battery performance is effectively achieved.

[0033] Among them, m2 / m1-n2 / n1 reflects the gradient difference in the proportion of lithium salt content in the free electrolyte and the non-free electrolyte. As the battery ages, the contents of various lithium salts in the electrolyte continue to change dynamically. However, the technical effect of the present application can only be guaranteed by ensuring that the first lithium salt A in the free electrolyte continues to dominate and that there is a sufficient amount of organic lithium salt in the non-free electrolyte to participate in the solvation reaction. The inventors found that if m2 / m1-n2 / n1 is too large or m2 / m1 is too large, not only will the battery polarization be too large, but the SEI film will also be very unstable, easily decomposed and destroyed and unable to be effectively regenerated, causing continuous decay of the cycle capacity; at the same time, m2 / m1-n2 / n1 should not be too small or n2 / n1 should not be too large, because the first lithium salt is required to have a unique effect of inhibiting the corrosion of the current collector substrate (such as aluminum foil). In contrast, although the high-content second lithium salt B can promote the formation of a stable SEI film, the corrosion problem of the current collector substrate (such as aluminum foil) caused will cause the battery's pole piece substrate to age, gradually lose its supporting function and conductive function, and aggravate the cycle decay. In summary, only by limiting m2 / m1-n2 / n1, m2 / m1, and n2 / n1 within the scope of this application can the technical effect of improving the battery RTE and the cycle capacity retention rate be achieved.

[0034] In the embodiments of the present application, the specific type of the first lithium salt is not specifically limited. As some preferred embodiments, the first lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), and lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6) is more preferred. The above-mentioned inorganic lithium salts all have the characteristics of wide redox window and excellent dissociation ability.

[0035] In the embodiments of the present application, the specific type of the second lithium salt is not specifically limited. As some preferred embodiments, the second lithium salt includes at least one of lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), and lithium (fluorosulfonyl) (trifluoromethylsulfonyl)imide (LiFTFS), more preferably lithium bis(difluorosulfonyl)imide (LiFSI). The above-mentioned types of organic lithium salts all have the characteristics of reducing to generate a SEI protective layer rich in inorganic and organic components.

[0036] According to some specific embodiments of the present application, the electrolyte is formed by secondary injection, and the secondary injection includes one injection of electrolyte and two injections of electrolyte; the one injection of electrolyte includes a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the one injection of electrolyte is MA1%, and the mass proportion of the second lithium salt in the one injection of electrolyte is MB1%; the two injections of electrolyte include the first lithium salt and the second lithium salt, the mass proportion of the first lithium salt in the two injections of electrolyte is MA2%, and the mass proportion of the second lithium salt in the two injections of electrolyte is MB2%, θ1=MB1% / MA1%, θ2=MB2% / MA2%, satisfying 0.05≤θ1≤1, 0≤θ2≤2, m2 / m1<θ1.

[0037] According to some further specific embodiments of the present application, 3≤MA1≤15, 5≤MA2≤15 are satisfied.

[0038] In an embodiment of the present application, one injection of electrolyte is used to generate an initial SEI film, and one injection of electrolyte is formed into a portion of the electrolyte remaining in the pores of the electrode and the diaphragm after the reaction, forming a non-free electrolyte in the initial state. The second injection of electrolyte is used to supplement the electrolyte required for long cycles. When one injection of electrolyte is excessive, the portion that has not been consumed or has not entered the pores of the diaphragm and the electrode merges with the second injection of electrolyte to form a free electrolyte in the initial state. The secondary injection flexibly controls the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery by separating the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage. Therefore, the secondary injection and the condition of m2 / m1<θ1 are the key to achieving the localized distribution characteristics of the electrolyte.

[0039] In the embodiment of the present application, one injection of electrolyte is mainly used for forming the initial SEI layer. If the first lithium salt in one injection of electrolyte is too low and the second lithium salt is too high, it will cause corrosion of the collector metal foil. Therefore, the upper limit of θ1 is less than or equal to 1, and the lower limit of MA1 is greater than or equal to 3; if the first lithium salt in one injection of electrolyte is too high and the second lithium salt is too low, the stability of the SEI layer will be insufficient, and the RTE of the battery cannot be effectively improved. Therefore, the lower limit of θ1 is greater than or equal to 0.05. The second injection of electrolyte is mainly used to supplement the ion channels required for long cycles. If the first lithium salt in the second injection of electrolyte is too low and the second lithium salt is too high, the electrolyte redox electrochemical window will be narrowed, the cycle consumption will be aggravated, and the RTE after the cycle will deteriorate. Therefore, the upper limit of θ2 is less than or equal to 2, and the lower limit of MA2 is greater than or equal to 5; if the first lithium salt in the electrolyte is too high, the desolvation energy barrier of lithium ions at the interface will be high, the impedance of the ion transport battery will be large, and the cycle capacity retention rate will be easily deteriorated due to lithium precipitation. Therefore, the upper limits of MA1 and MA2 in one injection of electrolyte and two injections of electrolyte are respectively defined.

[0040] According to some other specific embodiments of the present application, 0.2≤θ1 / Min(σc,σa,σs)≤2, 0≤θ2 / Max(σc,σa,σs)≤5 are satisfied; wherein, Min(σc,σa,σs) represents the minimum value among σc, σa and σs, and Max(σc,σa,σs) represents the maximum value among σc, σa and σs; σc represents the porosity of the positive electrode sheet when the battery is at 0% SOC; σa represents the porosity of the negative electrode sheet when the battery is at 0% SOC; σs represents the porosity of the diaphragm when the battery is at 0% SOC.

[0041] In the embodiments of the present application, the porosity of the positive electrode sheet, the negative electrode sheet and the separator is the key to restricting the electrolyte wetting ability and the lithium ion migration ability. Therefore, the minimum value of σc, σa and σs indicates that this part is the battery cell dynamics bottleneck. The purpose of regulating the relative mass content θ1 of the second lithium salt and the first lithium salt in an injection of electrolyte is also to achieve that the non-free electrolyte can not only uniformly infiltrate the positive and negative electrodes, uniformly form, but also avoid unnecessary lithium source consumption and improve the energy efficiency of the battery. When the porosity of the positive electrode sheet, the negative electrode sheet and the separator tends to be low, θ1 tends to be low and is subject to the minimum bottleneck Min(σc,σa,σs).

[0042] At the same time, the porosity of the positive electrode sheet, the negative electrode sheet and the diaphragm is also the key to ensure timely replenishment of the electrolyte and participate in the interfacial reaction. Therefore, the maximum value among σc, σa and σs indicates that this part is the bottleneck of electrolyte consumption and long life of the battery cell. The second injection regulates the relative mass content θ2 of the second lithium salt and the first lithium salt. Its purpose is also to achieve a high redox stability of the free electrolyte, reduce the impedance growth caused by side reactions in the cycle, and improve energy efficiency and cycle life. When the porosity of the positive electrode sheet, the negative electrode sheet and the diaphragm tends to be high, θ2 tends to be high and is subject to the maximum value bottleneck Max(σc,σa,σs).

[0043] The inventors found that if θ1 / Min(σc,σa,σs) is too large, it means that the pores of the pole piece and the diaphragm are not enough to support the rapid infiltration of the electrolyte, and the excessive second lithium salt in the non-free electrolyte is unevenly formed into a film, which is easy to cause low energy efficiency and poor cycle stability of the battery; if θ1 / Min(σc,σa,σs) is too small, it means that although the pores of the pole piece and the diaphragm are sufficient to ensure the rapid infiltration of the electrolyte, there is too little second lithium salt in the non-free electrolyte, and the film-forming ability is insufficient, which is also easy to cause battery cycle loss. If θ2 / Max(σc,σa,σs) is too large, it means that the pole piece has many reaction interfaces or the diaphragm has insufficient mechanical stability, the free electrolyte has a narrow redox window, and rapid consumption is missing during the long-term cycle process, resulting in a diving attenuation of the battery's cycle capacity and energy efficiency.

[0044] In summary, by limiting 0.2≤θ1 / Min(σc,σa,σs)≤2, 0≤θ2 / Max(σc,σa,σs)≤5, the RTE loss caused by the electrochemical polarization and concentration polarization of the battery can be greatly reduced, so that the RTE of the battery can reach more than 90% (25℃, 0.5P, 2.5V-3.65V), and up to 95%; at the same time, it can effectively enhance the interface protection of the positive and negative active materials, while improving the cycle capacity retention rate of the battery cell.

[0045] According to some other specific embodiments of the present application, 15%≤σc≤60%, 20%≤σa≤70%, 10%≤σs≤60%, thereby being able to meet the electrolyte wetting capacity and material mechanical strength of the positive electrode sheet, the negative electrode sheet and the separator.

[0046] In the embodiments of the present application, the above-mentioned battery can be used for both lithium-ion batteries and sodium-ion batteries. The following takes lithium-ion batteries as an example for explanation:

[0047] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, and the positive active material layer includes a positive active material. The specific type of the positive active material is not particularly limited. As some specific embodiments, the positive active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganese oxide, binary materials, and ternary materials.

[0048] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0049] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0050] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene-butadiene rubber (SBR).

[0051] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in an organic solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0052] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0053] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0054] In some embodiments of the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin-oxygen compounds, and tin alloys.

[0055] In some embodiments of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0056] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0057] In some embodiments of the present application, the negative electrode active material layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na) and the like.

[0058] In some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet (such as negative electrode active material, conductive agent, binder and any other components) are dispersed in an organic solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0059] The second aspect of the present application proposes a method for injecting liquid in a battery of one or more embodiments. According to the embodiments of the present application, the above-mentioned injection method includes: using one injection of electrolyte for the first injection, standing, and forming; using two injections of electrolyte for the second injection, high-temperature aging, and volume separation; one injection of electrolyte includes a first lithium salt and a second lithium salt, and the two injections of electrolyte include a first lithium salt and a second lithium salt, the first lithium salt is an inorganic lithium salt, and the second lithium salt is an organic lithium salt.

[0060] Specifically, the above-mentioned injection method includes:

[0061] S100: Use one injection of electrolyte for the first injection, let it stand, and then

[0062] In this step, an electrolyte is injected for the first time, left to stand, and formed to form an initial SEI film on the surface of the positive electrode active material and the negative electrode active material respectively. The part of the electrolyte remaining in the positive electrode plate, the negative electrode plate and the pores of the diaphragm after the electrolyte formation reaction forms a non-free electrolyte in the initial state.

[0063] S200: Use two injections of electrolyte for the second injection, high temperature aging, and capacity division

[0064] In this step, two injections of electrolyte are used for the second injection, high temperature aging, and volume separation to form the initial state of free electrolyte. When one injection of electrolyte is excessive, the part that is not consumed or does not enter the pores of the diaphragm, positive electrode sheet, and negative electrode sheet merges with the second injection of electrolyte to form the initial state of free electrolyte.

[0065] According to the injection method of the embodiment of the present application, the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage are separated by secondary injection, and the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery are flexibly controlled, which can effectively reduce the RTE loss caused by electrochemical polarization and concentration polarization, thereby effectively improving the battery's cycle energy efficiency (ie, RTE) and cycle capacity retention rate.

[0066] According to some specific embodiments of the present application, the mass proportion of the first lithium salt in one shot of electrolyte is MA1%, the mass proportion of the second lithium salt in one shot of electrolyte is MB1%, the mass proportion of the first lithium salt in two shots of electrolyte is MA2%, the mass proportion of the second lithium salt in two shots of electrolyte is MB2%, θ1=MB1% / MA1%, θ2=MB2% / MA2%, satisfying 0.05≤θ1≤1, 0≤θ2≤2, m2 / m1<θ1. One shot of electrolyte is mainly used for chemical formation of the initial SEI layer. If the first lithium salt in one shot of electrolyte is too low and the second lithium salt is too high, it will cause corrosion of the collector metal foil. Therefore, the upper limit of θ1 is limited to less than or equal to 1, and the lower limit of MA1 is greater than or equal to 3; if the first lithium salt in one shot of electrolyte is too high and the second lithium salt is too low, it will cause insufficient stability of the SEI layer and fail to effectively improve the RTE of the battery. Therefore, the lower limit of θ1 is limited to greater than or equal to 0.05. The second injection of electrolyte is mainly used to supplement the ion channels required for long cycles. If the first lithium salt in the second injection of electrolyte is too low and the second lithium salt is too high, the electrolyte redox electrochemical window will be narrowed, the cycle consumption will be aggravated, and the RTE after the cycle will deteriorate. Therefore, the upper limit of θ2 is limited to less than or equal to 2, and the lower limit of MA2 is greater than or equal to 5; if the first lithium salt in the electrolyte is too high, it will lead to a high desolvation energy barrier for lithium ions at the interface, a large impedance of the ion transfer battery, and it is easy for lithium precipitation to lead to deterioration of the cycle capacity retention rate. Therefore, the upper limits of MA1 and MA2 in the first injection of electrolyte and the second injection of electrolyte are respectively limited.

[0067] In the embodiments of the present application, the electrolyte demand of the battery is related to the cell capacity, and the electrolyte demand can be represented by the injection coefficient (injection amount / cell capacity). According to some specific embodiments of the present application, the injection coefficient of the sum of one injection of electrolyte and two injections of electrolyte is 3g / Ah to 5g / Ah, and as an example, it can be 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah, 5g / Ah, etc. By limiting the injection coefficient to the above range, it can be ensured that the diaphragm and the positive and negative pole pieces are fully infiltrated, and the electrolyte will not swell or accumulate at the bottom of the battery due to excessive amount of electrolyte, causing local lithium precipitation. 3.5g / Ah to 5g / Ah is preferred.

[0068] According to some further specific embodiments of the present application, the mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2). By limiting the mass ratio of the first injection of electrolyte to the second injection of electrolyte within the above range, it can be ensured that the SEI protective layer formed by chemical formation is uniform and the local distribution characteristics of the non-free electrolyte and the free electrolyte of the present application can be achieved.

[0069] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the injection method of the above embodiment. As a result, the energy storage device has excellent cycle energy efficiency (ie, RTE) and cycle capacity retention rate. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.

[0070] Specifically, the energy storage device of the present application may include but is not limited to a battery module, a battery pack, a battery system, etc. In addition, the energy storage device of the present application may also include at least one of an electric energy storage device for the power generation side of the power system, an electric energy storage device for the power distribution side of the power system (such as an electrochemical energy storage device), and an electric energy storage device for the user side of the power system.

[0071] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric power equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric power equipment. As a result, the electric power system has excellent cycle energy efficiency (ie, RTE) and cycle capacity retention rate. It should be noted that the above-described features and advantages for the battery are also applicable to the electric power system and will not be repeated here.

[0072] The above-mentioned power consumption system may include but is not limited to mobile phones, tablet computers, laptop computers, desktop computers, smart bracelets, smart watches, e-readers, game consoles and other portable electronic devices. It may also include but is not limited to vehicles such as cars, trucks, cars, vans, motor vehicles, high-speed trains, electric vehicles, etc. In addition, it may also be various household appliances, such as but not limited to refrigerators, electric lights, air conditioners, etc.

[0073] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0074] Example 1-1

[0075] This embodiment provides a lithium ion battery, and the preparation method thereof includes:

[0076] 1) Preparation of positive electrode sheet:

[0077] The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (SP), and adhesive polyvinylidene fluoride (PVDF) were dispersed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 97:2.5:0.5 and mixed evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil. The coating weight per unit area of ​​the positive electrode slurry was 33 mg / cm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained.

[0078] 2) Preparation of negative electrode sheet:

[0079] The negative electrode active material artificial graphite, conductive carbon black (SP), thickener (CMC) and binder (SBR) were dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. The coating weight per unit area of ​​the negative electrode slurry was 16 mg / cm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained.

[0080] 3) Preparation of electrolyte:

[0081] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed in a mass ratio of 1:1:1, and the first lithium salt A and the second lithium salt B are added according to the design in the table. The weight ratio of the additives is 3% vinylene carbonate, 0.5% fluoroethylene carbonate, 0.5% vinyl sulfate, and 0.5% tris(trimethylsilyl) phosphate. Stir until completely dissolved. Except that the weight ratio of lithium salt in one shot and two shots of electrolyte changes according to the design in the table, the other components are designed the same in one shot and two shots of electrolyte.

[0082] 4) Preparation of isolation membrane:

[0083] A commercially available ordinary polyethylene film was used, and the manufacturer provided the membrane porosity σs value.

[0084] 5) Battery assembly:

[0085] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to separate the positive and negative electrode sheets, and then wound into a bare battery cell. After welding the pole ears, the battery cell is assembled into an outer package, and vacuum dried after hot pressing, and then a secondary liquid injection process is performed. Specifically, the first injection of electrolyte is performed, and the battery cell is packaged, left to stand, and formed; the second injection of electrolyte is performed, and the battery cell is left to stand at high temperature, and the capacity is tested, etc., and finally a soft-pack lithium-ion battery with a capacity of 3.2Ah is prepared.

[0086] The formation process adopts the following process: Step 1: the battery cell is allowed to stand in a 45°C formation cabinet for 10 minutes, and charged at a rate of 0.1C for 7 minutes to 1.17% SOC; Step 2: Stand for 3 minutes, and charge at a rate of 0.2C to 30% SOC.

[0087] Example 1-2 to Example 1-23

[0088] The preparation methods of Examples 1-2 to 1-23 are basically the same as those of Example 1-1, and the differences are detailed in Table 1.

[0089] Example 2-1 to Example 2-16

[0090] The preparation methods of Examples 2-1 to 2-16 are basically the same as those of Example 1-5, and the differences are detailed in Table 2.

[0091] Example 3-1 to Example 3-11

[0092] The preparation methods of Examples 3-1 to 3-11 are basically the same as those of Examples 1-5, and the differences are detailed in Table 3.

[0093] Comparative Example 1-1 to Comparative Example 1-5

[0094] The preparation methods of Comparative Examples 1-1 to 1-5 are basically the same as those of Example 1-1, and the differences are detailed in Table 1.

[0095] Comparative Example 2-1 to Comparative Example 2-2

[0096] The preparation methods of Comparative Examples 2-1 and 2-2 are basically the same as those of Examples 1-5, and the differences are detailed in Table 2.

[0097] In Table 1, the porosity of the fixed electrode and the diaphragm is σc=23%, σa=36%, σs=40%; the injection coefficient is 4.0g / Ah; the mass ratio of the first injection of electrolyte and the second injection of electrolyte is 7:3. The standing condition after the first injection is 45±5℃ for 24 hours, the formation temperature is 45℃, and the standing condition (high temperature aging) after the second injection is 45±5℃ for 24 hours. In Table 1, the types and mass proportions of the first lithium salt A and the second lithium salt B in the first injection and the second injection are listed respectively.

[0098] In Table 2, the porosity of the pole piece and the diaphragm is specifically listed; the injection coefficient, the injection ratio of the first injection and the second injection, the temperature and time parameters in the second injection are consistent with those in Table 1. In Table 3, the injection coefficient, the injection ratio of the first injection and the second injection are specifically listed; the temperature and time parameters in the second injection are consistent with those in Tables 1 and 2.

[0099] In Tables 2 to 3, the types and mass proportions of the first lithium salt A and the second lithium salt B in one shot and two shots in Examples 2-1 to 2-12, 3-1 to 3-10 are consistent with those in Example 1-5; the types and mass proportions of the first lithium salt A and the second lithium salt B in one shot and two shots in Examples 2-16 and 3-11 are consistent with those in Example 1-20; the types and mass proportions of the first lithium salt A and the second lithium salt B in one shot and two shots in Example 2-14 are consistent with those in Example 1-13; the types and mass proportions of the first lithium salt A and the second lithium salt B in one shot and two shots in Example 2-15 are consistent with those in Example 1-16; Example 2-16 is consistent with Example 1-18; the types and mass proportions of the first lithium salt A and the second lithium salt B in one shot and two shots in Comparative Example 2-1 and Example 1-10 are consistent; the types and mass proportions of the first lithium salt A and the second lithium salt B in one shot and two shots in Comparative Example 2-2 are consistent with those in Example 1-19.

[0100] In the above embodiments and comparative examples, the porosity design values ​​of the positive and negative electrodes and the separator in the table are obtained by adjusting the cold pressing pressure and the hot pressing pressure after winding.

[0101] The free electrolyte components and their contents, and the non-free (pore) electrolyte components and their contents of the lithium ion batteries of the above embodiments and comparative examples were tested and calculated, and the results are shown in Table 1, Table 2 and Table 3. The capacity retention rate λ and the post-cycle energy efficiency η of the lithium ion batteries of the above embodiments and comparative examples after 1000 cycles at 25°C 0.5P were tested and calculated, and the results are shown in Table 1, Table 2 and Table 3.

[0102] Free electrolyte composition test:

[0103] The battery with outer packaging was discharged with a current of 0.05C to 0% SOC (2.5V), and a notch of about 0.5cm was cut on the right side of the battery facing the positive pole, and the same notch was cut on the right side facing the negative pole, ensuring that the two notches were on the diagonal line, and the free electrolyte was poured into the fluoride bottle from the small opening on the side of the positive pole until the intermittent droplets flowed down and the time was 30s. The type and relative mass content of lithium salt in the collected electrolyte were tested using ion chromatography IC.

[0104] Non-free (pore) electrolyte composition test:

[0105] Remove the outer packaging, take out a single bare cell, quickly peel off the pole piece, put it into an aluminum-plastic bag, add enough acetonitrile solvent to completely immerse the pole piece, seal the aluminum-plastic bag containing acetonitrile solvent and pole piece, and let it stand at 35±10℃ for 3 days. Use ion chromatography IC test to collect the type and relative mass content of lithium salt in the electrolyte.

[0106] Pole piece porosity test:

[0107] The porosity of the target electrode is tested by the electrode porosity test method. Specifically, the bare cell is disassembled, the dry electrode (positive or negative electrode) is laid flat on a glass table, cut into a certain size, and the thickness of the electrode is measured with a micrometer to calculate the volume V1 of the electrode; then the electrode is placed in the test equipment, the gas valve is opened, helium is introduced, and the actual volume V2 of the electrode is tested; the porosity σc and σa of the electrode (positive or negative electrode) are obtained according to the formula (V1-V2) / V1*100%.

[0108] The diaphragm porosity test method is the same as the pole piece porosity test method and will not be repeated here.

[0109] Cycle performance test:

[0110] At 25℃, charge to 3.65V at 0.5P constant power, then discharge to 2.5V at 0.5P constant power. The capacity of the Xth cycle of charge and discharge is recorded as CC x 、DC x The energy of the Xth cycle of charge and discharge is recorded as CE x ,DE x , until X=1000, record the capacity and energy value of each cycle.

[0111] The battery cycle life is evaluated by the cycle capacity retention rate λ, λ = DC 1000 / DC3;

[0112] The battery RTE is evaluated by the post-cycle energy efficiency η, η = DE 1000 / CE 1000 .

[0113] Table 1 Relationship between design parameters of free electrolyte and non-free electrolyte and cycle capacity retention rate and energy efficiency

[0114]

[0115]

[0116] Table 1 shows the relationship between the design parameters of free electrolyte and non-free electrolyte and the cycle capacity retention rate and energy efficiency. It can be seen from Comparative Examples 1-1 and 1-4 that the cycle capacity retention rate obtained by the traditional use of a single lithium salt for secondary injection or the use of a combined lithium salt for single injection is less than or equal to 80%, and the energy efficiency is ≤85%. It can be seen from Comparative Examples 1-3 and 1-5 that the use of a combined lithium salt for secondary injection, but not satisfying -0.8<m2 / m1-n2 / n1<0.2 and 0.05≤m2 / m1<1, its cycle capacity retention rate and energy efficiency are not improved but seriously deteriorated. It can be seen from Comparative Example 1-2 that although secondary injection is used, it does not satisfy 0.1≤n2 / n1≤5, and its cycle capacity retention rate and energy efficiency are also poor.

[0117] It can be seen from Examples 1-1 to 1-23 that by adjusting the type and proportion of lithium salt in the first and second electrolyte injections, the cycle capacity retention rate and energy efficiency can be improved within the range of design parameters satisfying -0.8<m2 / m1-n2 / n1<0.2.

[0118] From Examples 1-1 to 1-2, it can be seen that when m2 / m1-n2 / n1 is too small, the cycle capacity retention rate and energy efficiency are poor, which may be caused by one or more reasons: the first lithium salt in one shot is too low, the second lithium salt in one shot is too high, or the first lithium salt in two shots is too high. When the first lithium salt in one shot is too low and the second lithium salt is too high, it will cause corrosion of the metal foil; when the first lithium salt in two shots is too high, the desolvation energy barrier of lithium ions at the interface is high, and the impedance of the ion transport battery is large, which will cause the degradation of the energy efficiency of the cycle and after the cycle.

[0119] From Examples 1-12 to 1-13, 1-18 to 1-20, it can be seen that m2 / m1-n2 / n1 is too large, and its cycle capacity retention rate and energy efficiency are poor, which may be caused by one or more reasons that the first lithium salt in one shot is too high, the second lithium salt in one shot is too low, or the first lithium salt in two shots is too low, or the second lithium salt in two shots is too high. When the first lithium salt in one shot is too high and the second lithium salt is too low, the SEI layer stability is insufficient and the RTE cannot be improved; when the first lithium salt in two shots is too low and the second lithium salt is too high, the electrolyte redox electrochemical window will be narrowed, the cycle consumption will be aggravated, and the RTE after the cycle will deteriorate.

[0120] It can be seen from Examples 1-13 and 1-18 that, despite strict limits on the proportion of lithium salt content in the first and second injections, the cycle capacity retention rate and post-cycle energy efficiency are still not significantly improved compared with those in Comparative Example 1-2. This shows that m2 / m1-n2 / n1 is still the most important, and satisfying -0.8<m2 / m1-n2 / n1<0.2 is the key parameter for ultimately improving the cycle and post-cycle energy efficiency.

[0121] It can be seen from Examples 1-21 to 1-23 that the first lithium salt (inorganic lithium salt) can play the role of a wide redox window and excellent dissociation ability, and the second lithium salt (organic lithium salt) has the characteristic of being able to play the role of reduction to generate a SEI protective layer rich in inorganic and organic components.

[0122] Table 2 Performance influence of pole piece and diaphragm porosity

[0123]

[0124]

[0125] Table 2 shows the performance impact of the porosity of the pole piece and the diaphragm. In the preparation process of the battery, except for the different porosity of the positive pole piece, all other things remain the same between Comparative Example 2-1 and Example 1-10; in the preparation process of the battery, except for the different porosity of the negative pole piece, all other things remain the same between Comparative Example 2-2 and Example 1-19; in the preparation process of the battery, except for the different porosity of the positive and negative pole pieces and the diaphragm, all other things remain the same between Example 2-16 and Example 1-21. By comparison, it is found that the pole piece porosity will also have an impact on the cycle capacity retention rate and the energy efficiency after the cycle. Under the premise of satisfying -0.8<m2 / m1-n2 / n1<0.2, 0.05≤m2 / m1≤1, 0.1≤n2 / n1≤5, the designed porosity and the lithium salt ratio in the first and second injections of the electrolyte can further improve the electrical performance. When the above range is not met, the electrical performance is still not ideal despite the adjustment of the pole piece and diaphragm porosity.

[0126] It can be seen from Examples 1-5 and Examples 2-1 to 2-12 that the porosity of the electrode and the diaphragm has little effect on the distribution of lithium salts in the non-free electrolyte and the free electrolyte. However, it can still be found from Table 2 that when the σc, σa, σs value range and 0.2≤θ1 / Min(σc, σa, σs)≤2, 0≤θ2 / Max(σc, σa, σs)≤5 are satisfied, the electrical properties are at a relatively high level.

[0127] Combined with the test data of Example 1-1 and Example 1-19 in Table 1, although the design values ​​of the porosity of the electrode and the diaphragm σc=23%, σa=36%, σs=40% are more commonly used in the industry, θ1 / Min(σc,σa,σs)=14.45 in Example 1-1 and θ2 / Max(σc,σa,σs)=8.00 in Example 1-20, the porosity of the electrolyte does not match that of the electrode and the diaphragm, which may also be the reason for the serious performance degradation.

[0128] By comparing Example 2-13 with Example 1-13, Example 2-14 with Example 1-16, and Example 2-15 with Example 1-18 (in the preparation process of the battery, the three groups are consistent with the same group except for the different electrode porosities), it can be seen that selecting appropriate electrode and diaphragm porosities to match the lithium salt concentration of the secondary injection can further improve the electrical performance of the battery. Example 2-16, which optimizes the electrode and diaphragm porosity based on Example 1-21, also improves its cycle capacity retention rate and post-cycle energy efficiency.

[0129] Table 3 Performance influence of injection coefficient and injection mass ratio of secondary injection electrolyte

[0130]

[0131] Table 3 shows the effects of the secondary electrolyte injection coefficient and injection mass ratio on the distribution of lithium salts in the free electrolyte and non-free electrolyte as well as the electrical properties.

[0132] As can be seen from Table 3, the injection coefficients of Examples 3-1 and 3-2 are too low, and their cycle capacity retention rate and post-cycle energy efficiency are both poor. This may be due to the low injection coefficient, the diaphragm and the pole piece cannot be fully infiltrated, resulting in a lack of film protection in the pole piece that did not enter the electrolyte during the formation stage. As can be seen from Table 3, the injection coefficient of Example 3-6 is too high, and its cycle capacity retention rate and post-cycle energy efficiency are both poor. This may be due to the high injection coefficient, the excessive amount of electrolyte and the liquid swelling, and the redundant electrolyte will accumulate at the bottom of the battery to cause lithium precipitation. Therefore, the injection coefficient is limited to the range of 3g / Ah to 5g / Ah, and the battery has a relatively excellent cycle capacity retention rate and post-cycle energy efficiency.

[0133] As can be seen from Table 3, the ratio of the injection volume of the first injection and the second injection of Example 3-7 is too low, and its cycle capacity retention rate and energy efficiency after the cycle are both poor. This may be due to the fact that the injection volume during the first injection is not enough for full infiltration, the SEI protective layer obtained by the formation is uneven, and there is no area where SEI is formed after the second injection and the electrolyte is electronically conductive, resulting in the decomposition and accumulation of electrolyte byproducts. As can be seen from Table 3, the ratio of the injection volume of the first injection and the second injection of Example 3-10 is too high, and its cycle capacity retention rate and energy efficiency after the cycle are both poor. This may be due to the low proportion of the second injection, and the free electrolyte components mainly come from the electrolyte components that have not been consumed in the first injection, which are basically the same as the non-free electrolyte components. At this ratio, there is basically no difference between the second injection and the traditional first injection, and it is difficult to achieve the design of a localized electrolyte.

[0134] It can be seen from Examples 3-2 to 3-5, 3-8 to 3-9 that within the appropriate range of injection coefficient and injection mass ratio, the influence of the distribution of lithium salts in the non-free electrolyte and the free electrolyte is very small and can be ignored. In Example 3-11, after finely adjusting the injection coefficient and the secondary injection mass ratio on the basis of Example 2-16, the cycle capacity retention rate and the energy efficiency after the cycle are also slightly improved.

[0135] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0136] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet, the electrolyte comprises a free electrolyte and a non-free electrolyte, and the non-free electrolyte comprises an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator; The free-state electrolyte includes a first lithium salt and a second lithium salt, the first lithium salt is an inorganic lithium salt, the second lithium salt is an organic lithium salt, the mass proportion of the first lithium salt in the free-state electrolyte is m1%, and the mass proportion of the second lithium salt in the free-state electrolyte is m2%; the non-free-state electrolyte includes a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the non-free-state electrolyte is n1%, and the mass proportion of the second lithium salt in the non-free-state electrolyte is n2%, satisfying -0.8<m2 / m1-n2 / n1<0.2, 0.05≤m2 / m1<1, 0.1≤n2 / n1≤5.

2. The battery according to claim 1, characterized in that The first lithium salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate and lithium hexafluoroarsenate; And / or, the second lithium salt includes at least one of lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide and lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide.

3. The battery according to claim 2, characterized in that The electrolyte is formed by secondary injection, and the secondary injection includes one injection of electrolyte and two injections of electrolyte; the one injection of electrolyte includes a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the one injection of electrolyte is MA1%, and the mass proportion of the second lithium salt in the one injection of electrolyte is MB1%; the two injections of electrolyte include a first lithium salt and a second lithium salt, the mass proportion of the first lithium salt in the two injections of electrolyte is MA2%, and the mass proportion of the second lithium salt in the two injections of electrolyte is MB2%, θ1=MB1% / MA1%, θ2=MB2% / MA2%, satisfying 0.05≤θ1≤1, 0≤θ2≤2, m2 / m1<θ1.

4. The battery according to claim 3, characterized in that Satisfies 3≤MA1≤15, 5≤MA2≤15.

5. The battery according to claim 3, characterized in that Satisfies 0.2≤θ1 / Min(σc,σa,σs)≤2, 0≤θ2 / Max(σc,σa,σs)≤5; Among them, Min(σc,σa,σs) means taking the minimum value among σc, σa and σs, and Max(σc,σa,σs) means taking the maximum value among σc, σa and σs; σc represents the porosity of the positive electrode sheet when the battery is in a 0% SOC state; σa represents the porosity of the negative electrode sheet when the battery is in a 0% SOC state; σs represents the porosity of the separator when the battery is at 0% SOC.

6. The battery according to claim 5, characterized in that 15%≤σc≤60%; and / or, 20%≤σa≤70%; And / or, 10%≤σs≤60%.

7. A method for injecting liquid into a battery as claimed in any one of claims 1 to 6, characterized in that: include: Use one injection of electrolyte for the first injection, let it stand, and form; Use two injections of electrolyte for the second injection, high temperature aging, and volume separation; The first electrolyte includes a first lithium salt and a second lithium salt, and the second electrolyte includes a first lithium salt and a second lithium salt.

8. The liquid injection method according to claim 7, characterized in that: The mass proportion of the first lithium salt in the one injection of electrolyte is MA1%, the mass proportion of the second lithium salt in the one injection of electrolyte is MB1%, the mass proportion of the first lithium salt in the second injection of electrolyte is MA2%, and the mass proportion of the second lithium salt in the second injection of electrolyte is MB2%, θ1=MB1% / MA1%, θ2=MB2% / MA2%, satisfying 0.05≤θ1≤1, 0≤θ2≤2, m2 / m1<θ1.

9. The liquid injection method according to claim 7, characterized in that: The mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2).

10. The liquid injection method according to claim 7, characterized in that: The total injection coefficient of the first injection of electrolyte and the second injection of electrolyte is 3g / Ah to 5g / Ah.

11. An energy storage device, characterized in that: A battery comprising the battery according to any one of claims 1 to 6 or a battery obtained by the injection method according to any one of claims 7 to 10.

12. An electricity system, characterized in that: include: Electrical equipment, and The energy storage device as claimed in claim 11, wherein the energy storage device supplies power to the electrical equipment.